ASPEK LINGKUNGAN DAN PEREKAYASAAN PROSES DAUR ULANG KALENG MINUMAN DAN ABU SEKAM PADI SEBAGAI MATERIAL KOMPOSIT MELALUI METODE METALURGI SERBUK - Deni S Khaerudini; Anggito P Tetuko; P Sebayang; Muljadi Muljadi (Jurnal Ecolab, 2009)
The use of recycling aluminum from beverage can and rice-hull ash (RHA) offers an alternative material is presentedin this work. The aluminum cans are cut in little flakes in 5 – 10 mm size with a shears, and then were milled to obtainfine powders. Milling process was conducted in vibratory disc mill with milling variation for 10 and 20 minute. RHAwas obtained by calcinations of the rice-hulls at 900oC during 2 h in electrical furnace under oxidizing atmosphere.While, SiC as another silica source was utilized. After obtained aluminium fine powder from beverage can as matrixand silica powder from rice-hull and SiC as reinforce, then the raw material were milled by powder metallurgy methodfor production of Al/SiCp composites. The reinforcement composition of SiC to RHA was 30:20% vol., while thevolume ratio of matrix to reinforce was 80 to 20. The specimen test was obtained by cold compaction at 300 MPa andsintering at 600oC under high purity nitrogen atmosphere with holding time for 1 h. The composites sample weresubmitted at mechanical tests and samples microstructures were analyzed by optical microscope. Experimentalresults obtained shows that the use of RHA was beneficial to avoid corrosion through the formation and subsequenthydration of the Al4C3 phase and this recycle composite sample have significant potential as alternative material forautomotive or mechanical tools application. For ecological and economic routes, it reduces the use of city landfillsas consequently of abundant of aluminium beverage can and rice-hull, and the technique utilized in this work is veryimportant for economized routes and consequently, less expensive, compared to conventional methods.